A Low Cost Finger-Vein Capturing Device - Syafeeza, Ahmad Radzi; Kwan, Lik Hou; Syazana Itqan, Khalid; Norihan, Abdul Hamid; Wira Hidayat, Mohd Saad; Zahariah, Manap (Asian Research Publishing Network (ARPN), 2016)
This paper is focusing on the development of a low cost finger-vein capturing device with Graphical User Interface (GUI). It is a device that will capture the human finger-vein image and will be used for biometric security purposes such as authentication, verification and identification. A near-infrared light (NIR) will be emitted by a bank of NIR Light Emitting Diodes (LEDs) which will penetrate the finger and are absorbed by the haemoglobin in the blood. The areas in which the NIR rays are absorbed (i.e. Veins) thus appear as dark regions in an image conveyed by a CCD camera located on the opposite side of the finger. The image captured is analyzed using Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) to determine the suitable potentiometer level and to determine the best finger-vein image.